An integrated production and financial planning model for a manufacturing company - Kızıl, Volkan (My University, 2001)
Şirketlerin gelişip büyümeleri, büyük ölçüde, bünyelerinde bulunan çeşitli bölümlerin uyum içinde çalışmasına bağlıdır. Bu bölümlerin herbiri kendi çıkarlarını gözetirken diğer bölümlerin çıkarlarının zedelenmesine neden olmaktadır. Bu nedenle, günümüz şirketlerinde görülen idari anlayış değişiklikleri, özellikle toplam kalite prensiplerini yalın şirket yapılarına uygulama çabaları sonucu, önceleri bağımsız üniteler olarak çalıştıkları düşünülen birçok şirket fonksiyonunun entegrasyon problemi gündeme gelmiştir. Buna bağlı olarak, karşılıklı eşgüdüm giderek önem kazanmış ve bütünleşik karar modellerine ilgi doğmuştur. Bu çalışmanın amacı, bir bütünleşik üretim planlama probleminde üretim ve finans bölümlerinin eşzamanlı olarak ele alınarak modellenmesidir. Geliştirilen çok dönemli, çok ürünlü model, son dönem nakit durumunu maksimizeyi amaçlayan bir şirketteki, üretim ve finans bölümlerini eş zamanlı ele alan bir bütünleşik üretim planlama modelidir. Buna ek olarak, örnek bir problem üzerinde, senaryo çalışmaları yapılmış ve modelin değişen parametrelerde ne tür bir davranış içine girdiği incelenmiştir.

The prosperity of a firm depends highly on the functional integration of its various departments. Each department will try to maintain its own narrowly defined benefit, while damaging the other department's perceived benefits. Therefore, the recent changes in the understanding of management systems and especially, the increasing efforts to install total quality magament concepts to leaner organizational structures have all given way to the integration of functional areas of companies that were once thought to be separate identities. Thus, a need for mutual coordination has appeared and integrated decision models have received considerable attention by both the practitioners and the researches. The aim of this study is to model an aggregate production planning model that considers the production and finance functions in a simultaneous manner. The developed multi-period, multi-product model considers the synergetic effects of production and finacial planning in functioning of a manufacturing company which has an objective of maximizing its terminal cash position. In addition, based on an example problem, sensitivity and scenario analysis are performed to determine how the model behaviour changes with changing parameters.
Keywords: ÜRETİM PLANLAMASI